Implementation of Maternal and Perinatal Death Surveillance and Response (MPDSR) in Developing Countries: A Scoping Review - Yanti, Isra; Hakimi, Mohammad; Sulistyaningsih (Journal of Public Health Sciences, 2025)
Despite the World Health Organization's continued advocacy for the adoption of Maternal and Perinatal Death Surveillance and Response (MPDSR) as a systematic approach to uncovering and addressing the root causes of maternal and perinatal mortality, death rates within these populations remain alarmingly high in many regions. The effectiveness of MPDSR varies widely across settings, often limited by weak health information systems, reporting delays, blame-oriented cultures, and poor follow-up of audit recommendations. This scoping review aims to examine the practical application of MPDSR across various real-world contexts, with a particular emphasis on the mechanisms for identifying, reporting, evaluating, and responding to maternal and perinatal deaths, as well as the factors that enable or hinder these processes. Peer-reviewed publications from the past decade were systematically retrieved from major databases, including PubMed, Wiley, and ScienceDirect. The review identified key barriers such as shortages of skilled personnel, incomplete documentation, and limited financial and monitoring resources, while effective MPDSR was facilitated by community engagement, clear reporting systems, and supportive policies. These findings highlight the need to strengthen workforce capacity, data systems, and governance to reduce preventable maternal and neonatal deaths.